Thermoresponsive ionic liquid for electrochemical low-grade heat harvesting. (January 2023) - Wu, Angyin; Li, Xiaoya; Lee, Donghoon; Li, Jia; Yun, Jeonghun; Jiang, Cheng; Li, Zongkang; Lee, Seok Woo
Abstract: Thermally regenerative electrochemical cycle (TREC) is a promising technology for low-grade heat harvesting by employing the thermogalvanic effect of the electrodes. Whereas the electrolytes applied in TREC systems have a negligible response to temperature variation. In this study, a thermoresponsive ionic liquid (TRIL) is added to an electrolyte to endow it with temperature-driven phase change behavior, and the electrolyte is then utilized in a copper hexacyanoferrate-based TREC system for ultralow-grade heat harvesting. The TREC system is operated between 10 and 30 °C across the phase change critical point (Tc), so that the solvation states of the ions varied during the charging and discharging process, and a high energy density of 1.30 J g −1 and high energy conversion efficiency of 1.32% (20.0% for the Carnot efficiency) are achieved. The energy efficiency is 10 times that achieved by the conventional non-TRIL system under the same conditions. Moreover, the Tc of the TRIL can be tuned according to the species and concentrations of the electrolyte salt, which enhances the feasibility and resilience of the TRIL-containing TREC system. This study provides a novel perspective for electrolyte design in electrochemical cells, promoting the applicability of electrochemical cells in high-performance ultralow-grade thermal energy harvesting systems. Graphical Abstract: ga1 Highlights: Thermoresponsive ionic liquid is first applied as the electrolyte in thermally regenerative electrochemical system. Both thermogalvanic effect and ion solvation state changes are involved in TREC, enhancing energy conversion efficiency. Critical temperature can be tuned via modifying the salt species and concentrations, realizing versatile applications.